Enhanced mechanical properties of a novel compatibilized recycled polyethylene terephthalate/polyamide 11 (rPET/PA11) blends - Z. I. Khan; U. Habib; Z. B. Mohamad; A. M. Raji (eXPRESS Polymer Letters)
This research investigates various proportions of a compatibilizer, joncryl®, in a newly developed blend of rPET/PA11 having 80 wt% rPET and 20 wt% PA11. The proposed blend exhibits unique and outstanding mechanical properties. A few of the significant benefits of carrying out this research work include recycling the highest amount of rPET, saving natural recourses, and encountering the environmental issues associated with the wastage of polymers. Five different proportions of joncryl® (0,1,2,3 and 4 phr) were introduced to the blend of rPET/PA11 through a twin-screw extruder and injection moulding machine. The blend interface studied by scanning electron microscope (SEM) indicated that joncryl® boosted the chain extension. The results of tensile strength, Young's modulus and flexural strength displayed the boost up in properties at all proportions; however, the properties at 2 phr of joncryl® were unique and exclusive. The tensile strength of blend at 2 phr (joncryl®) is remarkably increased from 26.8 MPa to 46.24 MPa with a uniquely increased strain% from 3.56% to 196%. Young's modulus is also significantly improved. The impact strength rose from 147.12 to 667.68 J/m